Organisation of Support in Aid Centre “Szczecin for Ukraine” (Centrum Pomocy “Szczecin – Ukrainie”) from a Research Perspective - Bugajska, Beata (Paedagogia Christiana, 2024)
This research aimed to show the process of establishing and organising the Aid Centre, and the scale of its support activities for Ukrainian refugees. The study was conducted using the analysis of existing data, references to the experiences of individuals engaged in creating and managing the Centre (problem-centred interview) and Ukrainian refugees’ opinions about the Centre’s functioning. A thematic analysis was applied (a qualitative analysis technique) to identify shared topics in the respondents’ answers. The analysis presented herein focused on five areas that are crucial to identify the experiences of staff who developed and run the Centre, viz., 1) the initial weeks of the Centre’s functioning, starting on 9 March 2022, 2) interpersonal relations within the team, 3) difficult situations, 4) situations motivating work and 5) expectations concerning the future functioning of the Centre.